2019
DOI: 10.33785/ijds.2019.v72i05.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in the functionality of the components from goat milk and its products

Abstract: The purpose of this review is to present inclusive information regarding the recent advancements in the functionality of the components from goat milk and its products. In view of the expected revenues from global goat milk and products touching USD 15 billion in 2024, there is an urgent need to capitalize on designed fermented dairy products from goats with increased participation of bioactive ingredients in goat milk which in turn lead to excellent biological effects in terms of higher therapeutic and nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…As one of the major contributors to nonbovine milk production, goat milk has drawn widespread attention in recent years. The global market revenues in 2024 are estimated to be approximately $15 billion with a compound annual growth rate of more than 7% from 2018 to 2024, indicating the increasing consumption of goat milk and dairy products. , It is well acknowledged that goat milk is an attractive substitute to cow milk because of its higher digestibility, less inflammation, and fewer allergens . More intriguingly, goat milk can improve the physiological functions of humans, particularly for infants and elderly .…”
Section: Introductionmentioning
confidence: 99%
“…As one of the major contributors to nonbovine milk production, goat milk has drawn widespread attention in recent years. The global market revenues in 2024 are estimated to be approximately $15 billion with a compound annual growth rate of more than 7% from 2018 to 2024, indicating the increasing consumption of goat milk and dairy products. , It is well acknowledged that goat milk is an attractive substitute to cow milk because of its higher digestibility, less inflammation, and fewer allergens . More intriguingly, goat milk can improve the physiological functions of humans, particularly for infants and elderly .…”
Section: Introductionmentioning
confidence: 99%
“…"Labneh'' is concentrated yogurt prepared from goat milk with high short and medium chain fatty acids. ''Kishk'' is also a traditional drink of Lebanon prepared from goat milk along with yogurt and bulghur (Naagar et al 2019). Salva et al (2011) showed that consumption of fermented goat milk (L. rhamnosus CRL 1505) by immune-compromised malnourished mice resulted in recovery of nutritional status, biochemical parameters and offer resistance against intestinal and respiratory infections.…”
Section: Fermented Milkmentioning
confidence: 99%